1996
DOI: 10.1029/96gl01326
|View full text |Cite
|
Sign up to set email alerts
|

Shock‐induced phase transition of MnO around 90GPa

Abstract: Shock compression experiments on single crystal MnO grown by the Verneuil method have been carried out for the pressure range of 41–114GPa using both propellant and two‐stage light‐gas guns. The shock states, recorded with the inclined mirror method, were analyzed by the free‐surface approximation and impedance‐match solution. The observed shock compression curve of MnO with the rock salt structure(B1) is found to be slightly more compressible than that measured statically to 60GPa using a diamond‐anvil cell. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Shock wave compression experiments on MnO have revealed that it undergoes an 8% volume collapse at a pressure of 90 GPa and an estimated temperature of 1000°C on the shock Hugoniot P-V curve. 12 Electrical conductivity experiments on MnO under shock compression up to 50 GPa revealed no evidence of metallization to this pressure. 13 In addition, recent simulations predict magnetic collapse 3 in MnO at 149 GPa, and stabilization of the metallic B8 ͑NiAs͒ phase 14 at pressures above 120 GPa.…”
Section: Introductionmentioning
confidence: 90%
“…Shock wave compression experiments on MnO have revealed that it undergoes an 8% volume collapse at a pressure of 90 GPa and an estimated temperature of 1000°C on the shock Hugoniot P-V curve. 12 Electrical conductivity experiments on MnO under shock compression up to 50 GPa revealed no evidence of metallization to this pressure. 13 In addition, recent simulations predict magnetic collapse 3 in MnO at 149 GPa, and stabilization of the metallic B8 ͑NiAs͒ phase 14 at pressures above 120 GPa.…”
Section: Introductionmentioning
confidence: 90%
“…The classic Mott insulator, MnO, exhibits metalization under pressure. This phase transition is accompanied by a simultaneous moment and volume collapse [3][4][5][6][7][8]. On the theory side, however, the physics of this phase transition is totally different for different methods; while DFT results indicate that the increase in band width controls the phase transition[9, 10] DMFT results, on the other hand, show that the main reason for metalization lies in the increased crystal field splitting[1].…”
mentioning
confidence: 99%
“…MnO crystallizes in the rock-salt structure and exhibits AFM order below 118 K. The shock data [16], and later Raman and optical studies [17], had identified a transformation in MnO in the neighborhood of 90-105 GPa. Transport [18], magnetic, structural and spectroscopic [19], and reflectivity [17] data all point to a first-order, insulator-metal Mott transition near 100 GPa with volume (v = V/V 0 ) collapse v = 0.68 → 0.63, and moment collapse (from ∼ 5μ B to 1μ B or less [19]).…”
Section: Mnomentioning
confidence: 96%